Presence of Clostridium difficile in poultry and poultry meat in Egypt. (June 2018) - Abdel-Glil, Mostafa Y.; Thomas, Prasad; Schmoock, Gernot; Abou-El-Azm, Kamel; Wieler, Lothar H.; Neubauer, Heinrich; Seyboldt, Christian
Abstract: C. difficile has been recognized as a potential zoonotic agent encouraging investigations of C. difficile prevalence and ribotypes in animals. Here we report the prevalence and diversity of Egyptian C. difficile in I) samples from healthy poultry (n = 50), II) samples from diseased poultry (n = 54), and III) poultry meat (n = 150). Thirteen isolates were obtained from seven healthy and five diseased animals, but no C. difficile was cultured from poultry meat. The isolated C. difficile strains belonged to 3 different PCR-ribotypes (039/2, 205 and 001/FLI01). The detection of strains related to RT 001 known for its ability to cause disease in humans makes poultry a potential reservoir for pathogenic C. difficile . Highlights: 104 poultry samples and 150 meat samples from Egypt were investigated for C. difficile . C. difficile prevalence in birds was 11.5% (12 of 104), 14% (7 of 50) for healthy and 9.3% (5 of 54) for diseased poultry. Three different PCR-ribotypes RT 039/2, RT 205 and RT 001/FLI01 were found. C. difficile was not found in poultry meat samples.